ASSESSMENT OF STUDENTS ON BIPA TEACHING MATERIALS SPECIAL MATERIALS OF AGRICULTURE - Defina Defina; Yumna Rasyid; Sakura Ridwan (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2019)
ASSESSMENT OF STUDENTS ON BIPA TEACHING MATERIALS SPECIAL MATERIALS OF AGRICULTURE Defina1), Yumna Rasyid2), Sakura Ridwan2)Institut Pertanian Bogor1) dan Universitas Negeri Jakarta2)email: defina@ipb.ac.id Abstract Every teaching and learning process needs to be evaluated. One aspect that is evaluated is teaching material that is prepared and used by the teacher. Evaluation of teaching material can be done by asking for an assessment of students (students) as users of the material. This study aims to describe the results of student evaluations of integrative and content-based Indonesian language teaching material models for specific purposes of agriculture for foreign speakers. This research is evaluative research. The evaluation used in learning is program evaluation and not learning outcomes. Respondents were 14 students of BIPA IPB Developing Country Partnership Program (KNB). Data analysis based on the feasibility evaluation category with three criteria, namely discarded, maintained with revision, and maintained. The results of the study are as follows. First, the results of student evaluations are subject to the draft teaching material in the high category, with details: draft one 4.0 (high); second draft 4.3 (high); and third draft 4.5 (very high). Secondly, the input submitted, namely the need to add a variety of listening tasks (draft first), variations in the overall form of the task (second draft), perfecting the task of listening, reading, and layout (third draft). Keywords: assessment, users, teaching materials BIPA, agriculture PENILAIAN MAHASISWA TERHADAP BAHAN AJAR BIPA MATERI KHUSUS PERTANIAN AbstrakSetiap proses belajar mengajar perlu dievaluasi. Salah satu aspek yang dievaluasi adalah materi ajar yang disusun dan digunakan oleh guru. Evaluasi materi ajar dapat dilakukan dengan meminta penilaian pemelajar (mahasiswa) sebagai pengguna dari materi tersebut. Penelitian ini bertujuan mendeskripsikan hasil penilaian mahasiswa terhadap model materi ajar bahasa Indonesia integratif dan berbasis isi untuk tujuan khusus pertanian bagi penutur asing. Penelitian ini adalah penelitian evaluatif. Evaluatif yang digunakan dalam pembelajaran adalah evaluasi program dan bukan penilaian hasil belajar. Responden adalah 14 orang mahasiswa BIPA IPB Program Kemitraan Negara Berkembang (KNB). Analisis data berdasarkan kategori evaluasi kelayakan dengan tiga kriteria, yakni dibuang, dipertahankan dengan revisi, dan dipertahankan. Hasil penelitian sebagai berikut. Pertama, hasil penilaian mahasiswa terdadap draf materi ajar pada kategori tinggi, dengan rincian: draf satu 4,0 (tinggi); draf kedua 4,3 (tinggi); dan draf ketiga 4,5 (sangat tinggi). Kedua, masukan yang disampaikan, yaitu perlu ditambahkan variasi tugas menyimak (draf kesatu), variasi bentuk tugas secara keseluruhan (draf kedua), menyempurnakan tugas menyimak, membaca, dan tata letak (draf ketiga). Kata kunci: penilaian, pengguna, materi ajar BIPA, bidang pertanian